2014
DOI: 10.1016/j.immuni.2014.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Serial Transfer of Single-Cell-Derived Immunocompetence Reveals Stemness of CD8+ Central Memory T Cells

Abstract: Maintenance of immunological memory has been proposed to rely on stem-cell-like lymphocytes. However, data supporting this hypothesis are focused on the developmental potential of lymphocyte populations and are thus insufficient to establish the functional hallmarks of stemness. Here, we investigated self-renewal capacity and multipotency of individual memory lymphocytes by in vivo fate mapping of CD8(+) T cells and their descendants across three generations of serial single-cell adoptive transfer and infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
252
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(271 citation statements)
references
References 70 publications
18
252
1
Order By: Relevance
“…In response to antigen-induced inflammation, thymic naïve T cells migrate from thymus to targeted tissues and are activated to become effector and memory T cells. Of note, the CD8 + memory T cells seed in bone marrow as adult stem cells after inflammation [45,46]. In our study, naïve T cells and central memory T cells were attracted to the bone marrow of Nestin-Cre; Wls c/c mice.…”
Section: Discussionmentioning
confidence: 49%
“…In response to antigen-induced inflammation, thymic naïve T cells migrate from thymus to targeted tissues and are activated to become effector and memory T cells. Of note, the CD8 + memory T cells seed in bone marrow as adult stem cells after inflammation [45,46]. In our study, naïve T cells and central memory T cells were attracted to the bone marrow of Nestin-Cre; Wls c/c mice.…”
Section: Discussionmentioning
confidence: 49%
“…However, elegant in vivo approaches using adoptive transfer systems of single murine CD8 + memory cells (Gerlach et al, 2013a;Graef et al, 2014) also argue in favor of a linear differentiation model. As similar experiments have not been conducted for CD4 + cells yet and are impossible in the human system, our data represent new insights into this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence that the quality of the T cell response against pathogens could be used as a correlate of protection, and the cytokine polyfunctionality of the CD8 + T cells is considered as an important parameter to determine this (26). Cytokine polyfunctionality of T cells is an important characteristic of the so-called central-memory T cells, and several studies indicated that the expansion potential of central-memory T cells is superior compared with effector-memory T cells in regard to expansion (27)(28)(29)(30)(31). Autocrine IL-2 production is part of the polyfunctional central-memory T cell profile, and our study now provides direct evidence that autocrine IL-2 production contributes to a greater expansion capacity of CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%